About the control of semiconducting properties of chromia: investigation using photoelectrochemistry and orientation mapping in a TEM. (4th May 2018) - Latu-Romain, L.; Parsa, Y.; Ollivier, M.; Mathieu, S.; Vilasi, M.; Renou, G.; Robaut, F.; Wouters, Y.
Abstract: The semiconducting properties of chromia, studied by photoelectrochemistry (PEC), are varied by oxidizing pure Cr as a function of temperature and oxygen activity. At 800 °C and a p(O2) of 10-14 atm, a single n-chromia is observed, while at 900 °C and a p(O2) of 10-12 atm a n- & p-layer is obtained. For intermediate conditions, an insulating stoichiometric Cr2O3 is identified at 850 °C for a p(O2) of 10-13 atm. The TEM investigation reveals a duplex morphology for every scales: an equiaxed (resp. columnar) morphology has been developed in the internal (resp. external) part. Between these two subscales, a textured chromia layer has been identified as the first layer to form. Finally, the association of TEM and PEC techniques permits the identification of major point defects. It is revealed that the morphology is only linked to the growth direction: anionic (resp. cationic) growth leads to equiaxed (resp. columnar) grains.